Membangun Game Edutainment “Pengenalan Komputer” Menggunakan Shuffle Random (SR) Dan Finite State Machine (FSM) Untuk Anak Tunagrahita Ringan - Pratiwi, Heny; Arfyanti, Ita; Sururi, M Za’iem (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Research to build an Edutainment Game "Introduction to Computers" for mild retarded children is a study designed for teachers to deliver material to special school students (SLB) with special needs such as children with visual impairment, hearing impairment, mental retardation, intellectual disability, autism and blindness. . In this game the player will be presented with a variety of learning menus about "Computer Devices" and a game menu consisting of a guessing picture quiz to train memory, then there are typing games and labyrinth games to develop motor movements and increase students' responses and interests. Shuffle and Finite State Machine randomization algorithms will be applied in this study, with the aim of arranging the image position to be randomized in the learning menu and typing games as well as randomizing the position of the main characters and enemies in the labyrinth game made in three levels. This is done to improve students' learning and curiosity. The technology applied in this research is intelligent agent (intelligent system) which has a game agent character that will accompany children to learn and play.